MOLECULAR DOCKING STUDIES OF OPENED-CHAIN ANALOGUES OF ANTIMYCIN A ASCASPASES INHIBITORS OF APOPTOSIS IN COLORECTAL CANCER 3 - Fadilah, Fadilah; Arsianti, Ade; Kusmardi, Kusmardi; Tedjo, Aryo (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Studies of open-chain analogues of antimycin A as caspase inhibitors of apoptosis by molecular docking approach through computeraided drug design. The novelty of this study is finding the potential antimycin A 3 3 analogues which structurally modified against caspases. Methods: In finding potential caspase inhibitor of apoptosis in colorectal cancer (CRC) by in silico approach has been utilized. Protein structure of caspase has been downloaded from Protein Data Bank (1SHJ). The minimized of caspase was ready for molecular docking analysis. Analogues of antimycin A as lead compounds were designed and assessed using Molsoft drug-likeness. Both protein and lignan derivatives were docked with Autodock 4.2. The best docking score was shown by the lowest binding energy. 3 Results: Analogues of antimycin A has been done by evaluating their physicochemical properties as lead compounds. From this assessment, it showed that analogue 2 (AMD2), intermediate amide 4 (AMD4) showed good compounds to be drug-likeness by following Lipinski's rule of five (RO5), while intermediate amide 3 (AMD3) and antimycin A 3 (AMY3) showed cannot followed in Lipinski's RO5. From molecular docking result, the most favorable binding of caspase was AMD4 and AMD2 based on its energy that AMD4 (−7.34 kcal/mol) has the best binding interaction compared to AMD2 (−7.33 kcal/mol), AMY3 (−7.26 kcal/mol), and AMD3 (−5.23 kcal/mol), respectively. 3 Conclusion: This studies demonstrated that the opened-chain analogues of antimycin A AMD2 and AMD4 as a promising candidates of caspase inhibitor of apoptosis in CRC. Keywords: Open-chain analogue, Antimycin A 3 , Caspase, Apoptosis, Anticolorectal cancer. 3,